Pengaruh pembebanan terhadap kecepatan kerja roll conveyor - Syafrizal Syafrizal; Adolf Asih Supriyanto (Universitas Muhammadiyah Metro, 2020)
Roll conveyor is one of goods transportation, especially for moving goods produced from the production location to storage places, mainly carried out in industrial areas and away from moisture. There is a conveyor roll transport that moves use gravity style, namely by making the angle of inclination between the moving source area to the targeted area, yet if the source area with the destination area, namely the storage of goods produced is horizontally flat, then a source is needed a driving source, one of them is using an AC / DC electric motor. Based on the results of testing the conveyor roll by giving a different loading is the no-load condition of a 60 Watt electric motor can be rotated 73.2 rpm until the motor is finally able to deliver products with a load of 738,693 N with 71.4 rpm rotation. This test shows that the decrease in roll rotation occurs in the range of 0.22%, for an increase in the load of 49.05 N (5 kg). The graph results of the connection between loading and roller rotation show that the conveyor roll has a possibility to carry loads with a mass of about 150 kg.Keywords: conveyor roll, transportation, electric motor, rotation, load.